Employee Green Behavior as a Unidimensional Construct: Psychometric Evidence from Higher Education Institutions - AlOwais, Abdelaziz Abdalla; Suliman , Abubakr (International Review of Management and Marketing, 2026)
Employee Green Behavior (EGB) refers to voluntary and task-related environmentally responsible activities performed by employees in an organizational setting. Although EGB is conceptually multidimensional (comprising task-related behaviors, initiative, civic engagement, and helping), past research indicates that it can be conceptualized as a unidimensional phenomenon due to high levels of conceptual and empirical overlap. This research is expected to confirm the application of the unified 15-item EGB scale within Emirati Higher Education Institutions (HEIs), addressing a gap in the literature on environmental and social psychology. A cross-sectional survey was carried out on 170 members of faculty and administrative staff using a 5-point Likert scale questionnaire. R software was used for exploratory factor analysis (EFA), confirmatory factor analysis (CFA), reliability analysis, and validity analysis (convergent and discriminant) to analyze the data. The findings suggest that the 15 proposed items can be summarized into one latent factor with a high level of internal consistency (Cronbach’s alpha: 0.90) and acceptable levels of convergent validity (AVE =.50). The results affirm that there is no need to split the EGB into several dimensions according to collectivist and collaborative organizational culture. The scale reviewed is a validated unidimensional scale that can be used as a reliable, situation-specific measure of employee pro-environmental behavior, which can be used to inform evidence-based sustainability interventions and further our knowledge of environmental and social psychology in the context of higher education.